GIS-based analysis of lichen mappings and air pollution in the area of Reutlingen (Baden-Wurttemberg, Germany) - Jürgen Ulshöfer; Hans-Joachim Rosner (Meteorologische Zeitschrift, 2001)
Lichens on apple trees were used as bioindicators of air pollution in the region of Reutlingen (SW Germany). A lichen derived Index of Air Purity (IAP) according to LE BLANC and DE SLOOVER (1970) is compared with other data concerning air pollution and regional climate by using a Geographical Information System (GIS). Besides data from recording gauges and fog risk, a digital terrain model and landuse informations are integrated into the study. On subregional scale the correlation between the IAP-values and the air pollution measurements is poor. The applied method for the derivative of IAP-values seems to be insufficient to indicate regional pollution differences. Aus der Region um Reutlingen (SW-Deutschland) liegen Flechtenkartierungen an ApfelbÄumen vor, aus denen ein Luftreinheitsindex (Index of Air Purity-IAP) nach der Methode LE BLANC und DE SLOOVER (1970) berechnet wurde. Diese Informationen werden mit anderen Geo-Daten (Luftverschmutzung, Regionalklima, GelÄndemodell, Landnutzung, etc.) unter Verwendung eines Geographischen Informationssystemes (GIS) gemeinsam analysiert. Auf der gewÄhlten, subregionalen Maßstabsebene korrelieren die gemessenen Luftschadstoffwerte und die Kartierungsergebnisse nur gering. Dies fÜhrt zur Annahme, dass die nach der o.g. Methode abgeleiteten IAP-Werte nur mit Vorsicht auf regionaler Ebene anwendbar sind.